2010
DOI: 10.1111/j.1365-2982.2010.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of intestinal inflammation in mice lacking interleukin 10 by deletion of the serotonin reuptake transporter

Abstract: Background-Enterochromaffin cells and enteric neurons synthesize and release serotonin (5-HT). Reuptake, mediated by a plasmalemmal transporter (SERT) terminates the action of released 5-HT. Serotonin secretion and serotonin reuptake transporter (SERT) expression have been reported to be decreased in TNBS-induced experimental colitis and in patients with ulcerative colitis. The present study was designed to utilize the transgenic deletion of SERT as a gain-offunction model to test the hypothesis that 5-HT is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 30 publications
(83 reference statements)
5
55
0
1
Order By: Relevance
“…Recently, we have shown that TPH1-deficient (TPH1 2/2 ) mice, which have significantly lower amounts of 5-HT in the gut, exhibit reduced severity of colitis in two different models of experimental colitis (induced by dextran sulfate sodium [DSS] and dinitrobenzene sulfonic acid [DNBS]), whereas replenishing 5-HT levels upregulated colitis severity (24). A proinflammatory role for 5-HT has also been demonstrated in other studies where chemicalinduced colitis or spontaneous colitis associated with an IL-10 deficiency is increased in severity when coupled with the 5-HTenhancing effects of a knockout of the serotonin reuptake transporter, SERT (25,26). We have also shown that 5-HT plays a key role in the activation of immune cells to produce proinflammatory cytokines (24,27).…”
mentioning
confidence: 98%
“…Recently, we have shown that TPH1-deficient (TPH1 2/2 ) mice, which have significantly lower amounts of 5-HT in the gut, exhibit reduced severity of colitis in two different models of experimental colitis (induced by dextran sulfate sodium [DSS] and dinitrobenzene sulfonic acid [DNBS]), whereas replenishing 5-HT levels upregulated colitis severity (24). A proinflammatory role for 5-HT has also been demonstrated in other studies where chemicalinduced colitis or spontaneous colitis associated with an IL-10 deficiency is increased in severity when coupled with the 5-HTenhancing effects of a knockout of the serotonin reuptake transporter, SERT (25,26). We have also shown that 5-HT plays a key role in the activation of immune cells to produce proinflammatory cytokines (24,27).…”
mentioning
confidence: 98%
“…Human monocytes release different cytokines and chemokines, mainly via 5-HT 3 , 5-HT 4 and 5-HT 7 activation (35). Past studies also showed that 5-HT increase production of the pro-inflammatory cytokine IL-6 in mature Dendritic cells (DCs) via 5-HT 3 , 5-HT 4 and 5-HT 7 (8,9). And DCs are known to produce different chemokines thereby regulating the traffic of Th1 and Th2 cells into inflamed tissue (36).…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of 5-HT in the body is secreted from EC cells which are located within the mucosal mucosa, and the tryptophan hydroxylase (TPH) which in EC cells is the rate-limiting enzyme in the 5-HT synthesis process (5)(6)(7). Moreover, recent studies indicated that CD4 + T cells played an important role in the development of colonic EC cell hyperplasia in intestinal infection, and EC cells were influenced by helper T-cell subtype 1 (Th1) or subtype 2 (Th2) cytokine predominant environments (8,9). Cynaropicrin ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine IL-10 suppresses the expression of Th1-derived cytokines and plays as an important immune regulator in the intestinal tract 22 . Cellular gene therapy remains highly investigational, difficult, and expensive…”
Section: Discussionmentioning
confidence: 99%